Computational methodology for chirality determination in the Soai reaction by crystals: γ-glycine - Carter, Damien; Kahr, B.; Rohl, Andrew (Springer-Verlag 2007, 2012)
The autocatalytic Soai reaction gives abundant evidence of the enantioselective adsorption of organic compounds on a variety of crystals. Computational modelling can provide insight into mechanisms of enantioselectivity. Here, we use a combination of simulated annealing, forcefield, and quantum mechanical methods to examine interactions of pyrimidyl-5-carbaldehyde and 2-methylpyrimidyl-5-carbaldehyde with surfaces of γ-glycine. Using binding energy results, we predict the exposure of the pro-stereogenic S face of pyrimidyl-5-carbaldehyde (~65%) and 2-methylpyrimidyl-5-carbaldehyde (>90%) on the (1 Ī 0) and ( Ī 1 0) surfaces. The aim is to develop a robust computational methodology that can be applied to understanding crystal-biased asymmetric synthesis.